Pravo EU kot argument za posebno pravno ureditev regulativnih oblasti - Ferčič, Aleš (Podjetje in delo, 2024)
The article presents EU law as an argument for a special legal arrangement of national regulatory authorities. In this regard, it highlights the EU rules governing the status and special characteristics of national regulatory authorities, namely in various socially important areas, and then focuses on the standards of independence as determined by Directive 2019/944/EU and Directive 2024/1788/EU in the fields of electricity and natural gas (market). As being EU legislative acts, the said directives principally take precedence over Slovenian legislative acts and other legal acts forming our legal system. In this regard, the author points out that, for example, the legislative act governing the salary system in (Slovenian) public sector must not prevent the full effect and application of EU law in the area under consideration.
Keywords: bančni in finančni sektor; banking and financial sector; energetski sektor; energy sector; EU law; independence; insurance sector; neodvisnost; postal sector; poštni sektor; pravo EU; regulativna oblast; regulatory authority; sectoral regulator; sektorski regulator; telecommunications sector; telekomunikacijski sektor; transport sector; transportni sektor; zavarovalni sektor